The structural response of a bunker subjected to blast loading - Mohd Pilus, Mohd Nordin (2007)
In recent years there is an increasing incidence of bomb attacks on civil engineering structures which frequently caused substantial damage or even collapse of structures. Such incidence always results in economic loss and more seriously loss if life. This clearly indicates that it is timely for structural engineers to consider blast loads in their design. There are substantial costs incurred in designing structures against blast loads. Therefore there are only a certain category of structures which require such design in accordance to the level of protection required. In this paper a reinforced concrete bunker was used to represent such structure, whereby its structural response to an external explosion of a surface charge was investigated. The blast load was theoretically generated based on the explosion of 300 kg of TNT at a distance of 50 meters from the structure. Both linear and non-linear analyses were conducted using a computer program considering the dead load alone as well as the combination of dead and blast loads. The program utilizes the finite element method which provides results in the form of nodal displacements and stress resultants. As expected, the linear analysis gave lower results than the non-linear analysis. Linear analysis is only applicable in the linear elastic range and is unreliable when extreme loadings are involved. Since the blast loads caused severe effect on structures, non-linear analysis is more appropriate for the purpose. Blast load causes a tremendous increase of stress levels in structures,indicating the severity of the loading. This is due to the fact that such load acts as moving pulses loading only a small part of the structure at a time. Therefore the structure must be design to resist the high stress levels.